Difficulties Faced by Organisations When Implementing a Six Sigma Programme: A Case Study of an Organisation in Malaysia - Ornelas, Antonio Alexandre de (2010)
Purpose: The purpose of this study is to present a detailed investigation of the Six Sigma concept, including its history, methodologies and tools. Additionally, the difficulties faced by one organisation in Malaysia during the implementation of Six Sigma will be presented and some possible strategies to overcome them will be proposed. Design/Methodology/Approach: A detailed review of the literature was conducted to study the Six Sigma concept. The single case study approach was used on an organisation in Malaysia and data was collected from multiple sources. In-depth interviews with key employees of the company were conducted to understand the difficulties that the organisation faced during the Six Sigma implementation. Findings: Implementation of Six Sigma was found to be challenging. In spite of the company having had implemented Six Sigma in other subsidiaries around the world, the implementation in Malaysia, even though considered to be successful, faced certain difficulties and challenges. The main difficulties identified by the research were cultural change, communication, linking Six Sigma directly to customers and suppliers and understanding of Six Sigma tools and techniques. Research Limitations/Implications: This research has the usual limitations of a single case study. Its findings should be used by others as insights and additional information and should be generalized with care. This paper provides a source of information and reference that can be used by other organisations that are in the process of planning for implementation of Six Sigma Originality/Value: The research contributes to the existing literature on Six Sigma by adding a perspective of the difficulties faced by an organisation within a Malaysia context. This is a resource for professionals who are about to embark in the implementation process of Six Sigma in their organisations. This research can provide insights in order to anticipate some of the possible challenges organisations may face in such process and evaluate the strategies that were proposed.